2016
DOI: 10.1007/s10903-016-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Accessing Mental Health Services Among Culturally and Linguistically Diverse (CALD) Immigrant Women in Australia: Policy Implications

Abstract: Immigrant and refugee women from diverse ethnic backgrounds encounter multiple barriers in accessing mental healthcare in various settings. A systematic review on the prevalence of mental health disorders among culturally and linguistically diverse (CALD) women in Australia documented the following barriers: logistical, language and communication, dissonance between participants and care providers and preference for alternative interventions. This article proposes recommendations for policies to better address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 23 publications
5
76
0
Order By: Relevance
“…Some studies from this review found that negative attitudes towards professional help, including doubt and fear about treatment, personal characteristics of the provider (e.g., lack of providers with same ethnic background, language barriers), and a lack of trust in providers impeded the help‐seeking process . These concerns have been identified in previous reviews of barriers to help seeking for other mental health problems suggesting that individuals perceive the characteristics of the potential help resource (e.g., ability to help, credibility, race) as very important . In addition, Becker et al highlighted how social stereotypes could act as a barrier to care and how experiences were qualitatively different for those who were in a minority group compared with those who were not.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Some studies from this review found that negative attitudes towards professional help, including doubt and fear about treatment, personal characteristics of the provider (e.g., lack of providers with same ethnic background, language barriers), and a lack of trust in providers impeded the help‐seeking process . These concerns have been identified in previous reviews of barriers to help seeking for other mental health problems suggesting that individuals perceive the characteristics of the potential help resource (e.g., ability to help, credibility, race) as very important . In addition, Becker et al highlighted how social stereotypes could act as a barrier to care and how experiences were qualitatively different for those who were in a minority group compared with those who were not.…”
Section: Discussionmentioning
confidence: 76%
“…12,14,17,18,24,40 These concerns have been identified in previous reviews of barriers to help seeking for other mental health problems suggesting that individuals perceive the characteristics of the potential help resource (e.g., ability to help, credibility, race) as very important. 29,[54][55][56] In addition, Becker et al 26 highlighted how social stereotypes could act as a barrier to care and how experiences were qualitatively different for those who were in a minority group compared with those who were not. Their study showed that participants from a nonminority group reported that family members and clinicians failed to view eating disorders as of clinical concern, but participants from ethnicminority backgrounds reported that clinicians did not believe that eating disorders occurred in certain groups such as African-Americans.…”
Section: Perceived Barriers and Facilitators Towards Help-seeking For Edmentioning
confidence: 99%
“…Refugee youth more likely to turn to informal help than professional help. Negative expectations about seeking help, need for autonomy and structural barriers faced by refugees.Wohler et al 2017[56]Systematic reviewSystematic review into barriers culturally and linguistically diverse women face in accessing mental health services in Australia.Mental health servicesWhen accessing mental health services in Australia, culturally and linguistically diverse women (including refugees) face language and communication barriers, logistical barriers, barriers of cultural dissonance and have a preference for alternative interventions.Yelland et al 2014[57]QualitativeResponsiveness of health services to the social and mental health of Afghan women and men at the time of having a baby.City of Greater Dandenong and City of Casey, VictoriaMaternal and child health servicesSemi-structured interviews (focus groups were only with service providers)30Afghanistan (30)Participants stated they were not asked about social circumstances despite social hardship during the antenatal and postnatal period.Yelland et al 2016[58]QualitativeAfghan refugee and service providers’ experiences of language support during pregnancy check-ups, labour and birth.VictoriaMaternity servicesInterviews (focus groups were only with service providers)30Afghanistan (30)There was a lack of use of interpreters with family members often interpreting.…”
Section: Resultsmentioning
confidence: 99%
“…Over and above structural barriers to treatment such as availability and funding of qualified interpreters, or insurance coverage of psychotherapists, socio-cultural barriers are to be considered when treatment is enabled. Several studies showed that the cross-cultural setting might be a challenge to provide appropriate mental health care to refugees and asylum seekers for a variety of reasons such as stigma, taboo, trust issues, and a mismatch between Western concepts of diagnosis and treatment and the problems and needs perceived by refugees and asylum seekers [4,40,[65][66][67][68][69][70][71][72]. Moreover, the expression of the perceived problems, idioms of distress, or symptom expression of common mental disorders can vary substantially within and between cultural backgrounds and may decrease the accuracy of diagnostic appraisals and treatment outcome [73][74][75][76].…”
Section: Barriers To More Frequent Treatment Of Refugees and Asylum Smentioning
confidence: 99%